Turnover of labile and recalcitrant soil carbon differ in response to nitrate and ammonium deposition in an ombrotrophic peatland - CURREY, PAULINE M; JOHNSON, DAVID; SHEPPARD, LUCY J; LEITH, IAN D; TOBERMAN, HANNAH; van derWAL, RENÉ; DAWSON, LORNA A; ARTZ, REBEKKA R.E (Global change biology, 2010)
The effects of 4 years of simulated nitrogen deposition, as nitrate (NO₃⁻) and ammonium (NH₄⁺), on microbial carbon turnover were studied in an ombrotrophic peatland. We investigated the mineralization of simple forms of carbon using MicroResp[trade mark sign] measurements (a multiple substrate induced respiration technique) and the activities of four soil enzymes involved in the decomposition of more complex forms of carbon or in nutrient acquisition: N-acetyl-glucosaminidase (NAG), cellobiohydrolase (CBH), acid phosphatase (AP), and phenol oxidase (PO). The potential mineralization of labile forms of carbon was significantly enhanced at the higher N additions, especially with NH₄⁺ amendments, while potential enzyme activities involved in breakdown of more complex forms of carbon or nutrient acquisition decreased slightly (NAG and CBH) or remained unchanged (AP and PO) with N amendments. This study also showed the importance of distinguishing between NO₃⁻ and NH₄⁺ amendments, as their impact often differed. It is possible that the limited response on potential extracellular enzyme activity is due to other factors, such as limited exposure to the added N in the deeper soil or continued suboptimal functioning of the enzymes due to the low pH, possibly via the inhibitory effect of low phenol oxidase activity.